The Influence of Leadership, Adiwiyata Culture, and Project-Based Learning on Students' Environmental Character - Ary Wibowo; Hikmah Eva Trisnantari; Ria fajrin Rizqy Ana (Salus Publica: Journal of Community Service, 2026)
This study aims to analyze the effect of school farming project-based IPAS learning, Adiwiyata school culture, and principal leadership on the formation of students' environmental awareness. The study uses a quantitative approach with an ex-post facto design. The research subjects were 27 fourth, fifth, and sixth grade students at Melis Public Elementary School, Trenggalek Regency. Data analysis used multiple linear regression. The results showed that simultaneously, the three variables had a 61.5% effect on students' environmentally conscious character. Partially, the Adiwiyata school culture and principal leadership had a significant positive effect, while project-based IPAS learning did not show a significant partial effect.